Essentials of risk management - Crouhy, Michel, 1944-; Galai, Dan; Mark, Robert (Robert M.) (New York: McGraw Hill, 2024)
"The definitive guide to quantifying risk vs. return--fully updated to reveal the newest, most effective innovations in financial risk management"--
Includes bibliographical references, afterword and index.
Keywords: Risk management; Gestion du risque; Risk management; Risk management